Active transport of rhodamine 123 by the human multidrug transporter P‐glycoprotein involves two independent outer gates. Issue 2 (31st March 2020) - Nasim, Fauzia; Schmid, Diethart; Szakács, Gergely; Sohail, Azmat; Sitte, Harald H.; Chiba, Peter; Stockner, Thomas
Abstract: Human P‐glycoprotein (P‐gp) is a multispecific drug‐efflux transporter, which plays an important role in drug resistance and drug disposition. Recent cryo‐electron microscopy structures confirmed its rotationally symmetric architecture, which allows dual interaction with ATP and substrates. We here report the existence of two distinct, symmetry‐related outer gates. Experiments were aided by availability of the X‐ray structure of a homodimeric eukaryotic homolog of P‐gp from red alga (CmABCB1), which defined the role of an apical tyrosine residue (Y358) in outer gate formation. We mutated analogous tyrosine residues in each half of the human full‐length transporter (Y310, Y953) to alanine. These mutants were introduced in engineered transporters which bind rhodamine 123 in one of two symmetry‐related binding modes only. Outer gate dysfunction was detected by a loss of active transport characteristics, while these mutants retained the ability for outward downhill transport. Our data demonstrate that symmetric tyrosine residues Y310 and Y953 are involved in formation of two distinct symmetry‐related outer gates, which operate contingent on the rhodamine 123 binding mode. Hence, the rotationally symmetric architecture of P‐gp, which determines duality in ATP binding and rhodamine 123 interaction, also forms the basis for the existence of two independently operating outer gates.